Experimental drowning lung images on postmortem CT – Difference between sea water and fresh water. (March 2016) - Hyodoh, Hideki; Terashima, Ryuji; Rokukawa, Masumi; Shimizu, Junya; Okazaki, Shunichiro; Mizuo, Keisuke; Watanabe, Satoshi
Abstract : Highlights: Drowning models were prepared using sea water and fresh water, experimentally. All individuals were examined by ante- and post-mortem lung CT according to the time course. Ground-glass opacity presented in all cases, and also decreased lung aeration from 1 h to 24 h postmortem period. There was no significant difference in lung pattern on CT during the follow-up period. Postmortem lung CT could be used as an intra-cadaver documentation tool non-invasively. Abstract: Purpose: Experimental drowning models were prepared to investigate the time-related course of lung changes using postmortem CT. This study was approved by our institutional animal ethics committee. Materials and methods: Fifteen NZW rabbits (female fifteen, 2.6–4.3 (mean 3.3) kg) were divided into 3 groups: fresh water drowning (FRESH), sea water drowning (SEA), and sea water drowning with anterior chest compression (ACC). All individuals were examined by CT (Aquilion CX, Toshiba, Japan) on postmortem time course. The rabbit's head was submerged in a water bath for a total of 10 min. In ACC, cardiopulmonary resuscitation was performed for 2 min, additionally. The percentage of aerated lung volumes (%ALV = 100 (aerated lung volume/total lung volume)) were statistically evaluated and the lung CT image patterns and pleural fluid appearance time were investigated. Results: All lungs had decreased their %ALV within 24 h, and there were no statistical differences in and among the 3 groups. After 36 h, %ALV tended to increase in all groups, and only ACC presented a statistical difference between 1 h and 36 h ( p < 0.005). On postmortem lung CT, all lungs presented ground-glass opacity with interstitial thickening spread pattern (100%) and no pattern change during the follow-up period. After presenting pleural space fluid collection, the %ALV tended to increase. Conclusion: There were no differences among FRESH, SEA, and ACC in %ALV within 24 h. Only ground-glass opacity could be detected on postmortem lung CT, experimentally.